Physicochemical, Sensorial and Microbiological Characterization of PoroCheese, an Artisanal Mexican Cheese Made from Raw Milk † - González Ariceaga, Citlalli Celeste (Foods, 2019)
Poro cheese is a regional product originally from the area of Los Rios, Tabasco in Mexico. In the context of preserving the heritage of Poro cheese and protecting the specific characteristics that define its typicity through an origin designation, the present study was conducted to establish a general profile of Poro cheese by characterizing their physicochemical, textural, rheological, sensorial and microbiological characteristics. Differences in moisture, proteins, fats, NaCl, titrable acidity, pH, color texture and rheology amongst cheese factories were observed and ranges were established. Fifteen descriptors were generated to provide a descriptive analysis, eight of which were significantly different amongst the factories with no differences in the global acceptability of cheese. The favorite cheese had the highest scores for aroma attributes. Conventional and molecular methods were used to identify the main microorganisms, for which Lactobacillus plantarum, L. fermentum, L. farciminis and L. rhamnosus were the main microorganisms found in Porocheese. The obtained data constituted the parameters for characterizing Poro cheese, which will strongly help to support its origin appellation request process.